A numerical model of initial recombination for high-LET irradiation: Application to liquid-filled ionization chambers. (February 2016) - Aguiar, P.; Pardo-Montero, J.
Abstract: In this paper we present a numerical model of initial recombination in media irradiated with high linear energy transfer (LET) ions, which relies on an amorphous track model of ionization of high LET particles, and diffusion, drift and recombination of ionized charge carriers. The model has fundamental applications for the study of recombination in non-polar liquids, as well as practical ones, like in modelling hadrontherapy dosimetry with ionization chambers. We have used it to study the response of liquid-filled ionization chambers to hadrontherapy beams: dependence of initial recombination on ion species, energy and applied external electric field. Abstract : Highlights: Complete numerical model of initial recombination under proton/light ion irradiation (high-LET). Study of kinetics of initial recombination for proton/carbon irradiation. Application to hadrontherapy: liquid-filled ionization chambers irradiated by protons/carbon ions.